Experimental transmission of equine hepacivirus in horses as a model for hepatitis C virus. Issue 5 (24th February 2015) - Ramsay, Joshua D.; Evanoff, Ryan; Wilkinson, Tom E.; Divers, Thomas J.; Knowles, Donald P.; Mealey, Robert H.
Abstract : Equine hepacivirus (EHCV; nonprimate hepacivirus) is a hepatotropic member of the Flaviviridae family that infects horses. Although EHCV is the closest known relative to hepatitis C virus (HCV), its complete replication kinetics in vivo have not been described, and direct evidence that it causes hepatitis has been lacking. In this study, we detected EHCV in 2 horses that developed post‐transfusion hepatitis. Plasma and serum from these horses were used to experimentally transmit EHCV to 4 young adult Arabian horses, two 1‐month‐old foals (1 Arabian and 1 Arabian‐pony cross), and 2 foals (1 Arabian and 1 Arabian‐pony cross) with severe combined immunodeficiency (SCID). Our results demonstrated that EHCV had infection kinetics similar to HCV and that infection was associated with acute and chronic liver disease as measured by elevations of liver‐specific enzymes and/or by histopathology. Although most of these animals were coinfected with equine pegivirus (EPgV), also a flavivirus, EPgV viral loads were much lower and often undetectable in both liver and blood. Three additional young adult Arabian‐pony crosses and 1 SCID foal were then inoculated with plasma containing only EHCV, and evidence of mild hepatocellular damage was observed. The different levels of liver‐specific enzyme elevation, hepatic inflammation, and duration of viremia observed during EHCV infection suggested that the magnitude and course of liver disease was mediated by the virus inoculum and/or by host factors, including breed, age, and adaptive immune status. Conclusion : This work documents the complete infection kinetics and liver pathology associated with acute and chronic EHCV infection in horses and further justifies it as a large animal model for HCV. (Hepatology 2015;61:1533–1546)